It is better to Remain Small and Invisible. Informal Barriers to the Development of Small and Medium Enterprises in Belarus Part II - Papko, Aliaksandr (Warsaw Forum of Economic Sociology, 2017)
This paper is focused on informal relations between state authorities and business, which exist in a peculiar Belarusian economic system, where the competition remains restricted, and the public sector based on large companies continues to play a crucial role. The author argues that the Belarusian public authorities have developed a broad set of informal rules which allow them to extract resources from small and medium private enterprises (SMEs) and control the expansion of the private sector. He also argues that as long as informal extractive institutions designed and maintained by the state remain in place, the improvement of formal business regulations alone will not produce the expansion of the SME sector. In authors opinion, an extra-legal extraction of funds and informal discrimination against small and medium private enterprises are embedded in the logic of the centrally planned economy, which Belarus has preserved after the fall of the Soviet Union. This paper may also help to understand how SMEs operate in many other economies of the post-Soviet area and what obstacles to the development they face.